Two new species of Trigonotylus (Hemiptera: Heteroptera: Miridae: Stenodemini) from western Canada and northwestern United States - Scudder, G. G.e.; Schwartz, Michael D. (Zootaxa, 2012)
Two new species of stenodemine Miridae from western Canada and the United States are described. Trigonotylus exilis n.sp. from British Columbia to northern California and Utah, and T. setosus n. sp. from northern British Columbia, YukonTerritory, and adjacent northern Northwest Territories and Alaska are documented. A key to the species of Trigonotylusfrom this study region is provided to allow identification of the included fauna. Host plant species are identified. Lactic acid is proposed as an alternative to potash as a dissection medium for male genitalia.